Vaginal hysterectomy and plasty in the treatment of genital prolapse. - Rocca Gaggero, Ennio (2015)
Our experience in managing and Plasty Vaginal Hysterectomy to treat genital prolapse, conducted in 88 patients in the Department of Gynecology of the Archbishop Loayza (Hall 5-II) Hospital. Static principles on which the method is based and the different techniques used, their indications and contraindications listed are updated. In our series we emphasize the age, parity, clinical symptoms and degree of prolapse. We emphasize that vaginal hysterectomy and plasty, the indicated in premenopausal patients with pelvic relaxation grade II or III, using the technique de Mayo with some modifications.